PENGEMBANGAN E-MODUL INTERAKTIF PEMBUATAN POLA DASAR SISTEM DRESSMAKING PADA SISWA FASE E TATA BUSANA SMK NEGERI 1 KALITENGAH - Indah Kusuma Wardani; Imami Arum Tri Rahayu (JURNAL ILMIAH NUSANTARA, 2026)
Interactive e-modules are digital teaching materials that integrate text, images, audio, video, and interactive features, enabling students to learn independently. This study aimed to: (1) determine the feasibility level of the interactive e-module as a learning medium in basic pattern making using the dressmaking system for Phase E Fashion Design students at SMK Negeri 1 Kalitengah, and (2) determine students’ learning outcomes in basic pattern making using the dressmaking system through the implementation of the interactive e-module in learning basic pattern making using the dressmaking system for Phase E Fashion Design students at SMK Negeri 1 Kalitengah. This study employed the Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research was conducted at SMK Negeri 1 Kalitengah with 30 Phase E students of Grade X Fashion Design and Production as the trial subjects. Data collection techniques used expert validation sheets and learning outcome tests through cognitive and psychomotor assessments. The research instruments included validity assessment sheets, cognitive test questions, and psychomotor assessment sheets. The data analysis technique used descriptive quantitative analysis. The results showed that the interactive e-module obtained a “highly feasible” category with an average score of 3.68 from material experts, media experts, and language experts. Students’ learning outcomes showed a mastery level of 90%. Therefore, the interactive e-module is feasible and effective for use in learning basic pattern making using the dressmaking system.